2000
DOI: 10.1038/35019050
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a late chondritic veneer in the Earth's mantle from high-pressure partitioning of palladium and platinum

Abstract: The high-pressure solubility in silicate liquids of moderately siderophile 'iron-loving' elements (such as nickel and cobalt) has been used to suggest that, in the early Earth, an equilibrium between core-forming metals and the silicate mantle was established at the bottom of a magma ocean. But observed concentrations of the highly siderophile elements--such as the platinum-group elements platinum, palladium, rhenium, iridium, ruthenium and osmium--in the Earth's upper mantle can be explained by such a model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 23 publications
9
98
0
Order By: Relevance
“…Currently, however, it is not possible to find either a set or range of pressure-temperature conditions where metal-silicate partitioning at a single f O 2 can explain concentrations of all three groups of siderophile elements (Wood et al 2006). Highly siderophile elements, for example, remain excessively depleted in a homogeneous accretion scenario and require the addition of a final late veneer of material that did not undergo core formation (Holzheid et al 2000). Although it has been proposed that at high temperatures and pressures slightly siderophile (e.g.…”
Section: The Evolution Of Mantle F Omentioning
confidence: 99%
“…Currently, however, it is not possible to find either a set or range of pressure-temperature conditions where metal-silicate partitioning at a single f O 2 can explain concentrations of all three groups of siderophile elements (Wood et al 2006). Highly siderophile elements, for example, remain excessively depleted in a homogeneous accretion scenario and require the addition of a final late veneer of material that did not undergo core formation (Holzheid et al 2000). Although it has been proposed that at high temperatures and pressures slightly siderophile (e.g.…”
Section: The Evolution Of Mantle F Omentioning
confidence: 99%
“…The composition of the lithospheric mantle in terms of PGE and other chalcophile metals has been extensively documented and studied in the context of lithospheric age, tectonic/geodynamic setting, and the presence and composition of the late veneer event (e.g., Jagoutz et al, 1979;Morgan 1986;Pattou et al, 1996;Alard et al, 2000;Holzheid et al, 2000). Studies based on bulk rock geochemistry (e.g., Maier et al, 2012) may be prone to significant nugget effects because of the heterogeneous distribution of PGE-bearing microphases (Lorand et al, 2013), and thus detailed investigations that combine base metal sulphide petrography, mineral trace element compositions and isotopic systematics (particularly for the Re-Os system) are vital to assess the true complexity of the upper mantle sulphur and chalcophile element reservoir (e.g., Alard et al, 2000Alard et al, , 2005Aulbach et al, 2009;Griffin et al, 2002Griffin et al, , 2004Harvey et al, 2010;Lorand et al, 1990Lorand et al, , 2008Lorand et al, , 2010Luguet et al, 2003Luguet et al, , 2004Marchesi et al, 2013;Szabo et al, 1995;Wainwright et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental studies do not favor such high values for D Re (Ertel et al, 2001) and D Pt (Holzheid et al, 2000) compared with D Os (Borisov and Walker, 2000) but further experimental work is needed before a definitive answer can be given to this long-standing problem. Indeed, it was recently suggested that the abundance of moderately siderophile elements in Earth's mantle was set by equilibrium partitioning at model pressures (40 to 60 Gpa) and temperatures (2000 to 4000 K) much higher (Gessmann and Rubie, 2000;Li and Agee, 2001b) than those investigated by partitioning experiments of highly siderophile elements (Borisov and Walker, 2000;Holzheid et al, 2000;Ertel et al, 2001). One might also question whether metal segregated from silicate at uniform pressure and temperature.…”
Section: Discussionmentioning
confidence: 99%